Urinary Emmprin, matrix metalloproteinase 9 and tissue inhibitor of metalloproteinase 1 as potential biomarkers in children with ureteropelvic junction narrowing on conservative treatment. (March 2015) - Tian, Fengyan; Gu, Chaohui; Zhao, Zhanzheng; Li, Luping; Lu, Shan; Li, Zhenzhen
Abstract Background Rapid diagnosis and initiation of the treatment on congenital obstructive nephropathy are important for young children to slow down renal injury. The aim of our study was to investigate the role of urinary extracellular matrix metalloproteinase inducer (Emmprin), matrix metalloproteinase 9 (MMP‐9) and tissue inhibitor of metalloproteinase 1 (TIMP‐1) in the long‐term follow‐up of children with ureteropelvic junction (UPJ) narrowing on conservative treatment. Methods The study included 40 children with non‐obstructed hydronephrosis due to unilateral UPJ narrowing who were treated conservatively and followed up for 24 months. Voided urine samples were collected at diagnosis and at 3, 9, 15 and 24 months of follow‐up, respectively. Three enzymes concentrations were measured in urine. Results During the follow‐up, 25 children showed renal function stabilization (non‐obstructed group) and 15 children renal function deterioration (obstructed group). In the non‐obstructed group, a comparison between urine three enzymes levels at the last follow‐up and at baseline showed no significant differences (all P > 0.05). Glomerular filtration rate (GFR) and split renal function (SRF) showed similar trends. In the obstructed group, a comparison between the three enzymes levels at diagnosis and at basal condition showed a significant increase (all P < 0.01). But GFR and SRF showed a marked reduction at diagnosis (all P < 0.001). Receiver operator characteristic (ROC) analyses revealed a better diagnostic profile for uEmmprin, uMMP‐9 and uTIMP‐1 in identifying children with abnormal SRF (<40%) at 24 months of follow‐up [area under the curve (AUC) 0.877, 0.727 and 0.823, respectively]. Conclusions Urinary Emmprin, MMP‐9 and TIMP‐1 may be noninvasive potential biomarkers that could be used for long‐term follow‐up of children with UPJ narrowing on conservative treatment to determine those who might develop obstruction.